Context and novelty increase strength of auditory cues as a weak circadian zeitgeber in songbirds. (3rd July 2021) - Harpole, Clifford E.; Cassone, Vincent M.
ABSTRACT: Light is the best-studied external cue (zeitgeber) for the entrainment of circadian rhythms. Non-photic entrainment is also possible; some organisms can entrain to rhythmic temperatures, drug administration, feeding, water turbulence, exercise and social cues. One such social cue that has the capacity to act as a weak zeitgeber to songbirds is the rhythmic presentation of conspecific vocalization. To better characterize this phenomenon, we performed several trials in which male and female zebra finches were maintained in constant dim light and allowed to free-run for 1 week before being presented with different audio cues of various lengths of playback and audio design every day at the same time of day for 15–31 days. Live audio monitoring from a nearby colony housed in light: dark (LD) conditions proved the strongest zeitgeber we tested, suggesting the phenomenon is enhanced with dynamic, context-appropriate vocalizations. Live colony playback was more efficacious than was a 2 h or 4 h presentation of the same, single zebra finch song but not a 1 h presentation, suggesting that habituation may have occurred in some of these experiments. The monitoring of the colony was also not statistically different from a 4 h playback of that same song, reversed, suggesting that social context is not required. It was, however, more effective than a 4 h presentation of synthesized, pseudorandom tones. When birds entrained to the period of the zeitgebers, their expressed period closely matched 24 h with phases closely matched to the onset of the zeitgeber. Masking was not evident in contrast to masking observed following transfer from constant dim light to LD and vice versa. This series of experiments could prove a means of quantifying the capacity for reciprocal social interaction, a state which can be dynamic in songbirds, as well as the integration between sociality and the circadian clock.